Peningkatan Hasil Belajar Siswa Dalam Pembelajaran IPS Dengan Model Example Non Example di Sekolah Dasar - Leni Novriani; Arwin Arwin; Rifda Eliyasni (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The research is aimed to describe the plan, the implementation and the students’ learning outcomes in learning the Social Science Subject by using the Example non Example Model at 5th grade of SDN 19 Koto Tangah Padang. The classroom-action research was conducted in the research by using both qualitative and quantitative approaches. The subjects of the research were the teacher and 22 students of the school. The result of the research shows that: a) the lesson plan increased from 75% in cycle I to 93% in cycle II; b) in term of the teacher’s teaching aspect increased from 77% in cycle I to 95% in cycle II;c) the student’s learningoutcomes increased from 74,4 in cycle I to 84,1 in cycle II. Thus, the use of Example no Example model improves the student’s learning outcomes in learning the social science subjects at 5th grade of SDN 19 Koto Tangah Padang.